2004
DOI: 10.1002/prot.20261
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cysteine pKa values in creatine kinase and α1‐antitrypsin

Abstract: The structural determinants of the unusually low pK(a) values of Cys282 in human creatine kinase and Cys232 in alpha1-antitrypsin were studied computationally. We have demonstrated that hydrogen bonding to the cysteine residue is the prime determinant for both proteins. In the case of creatine kinase, the hydrogen bond donors are a serine side chain and an amide NH-group, while in alpha1-antitrypsin the donor is an amide NH. Each hydrogen bond lowers the pK(a) by between 0.8 and 1.5 pH units. The 1.1-unit lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 25 publications
5
37
0
Order By: Relevance
“…The factors contributing to the low pK a value are not all immediately apparent, although it was shown that a S…OH bond between Cys283 and Ser285 ( Figure 2A) contributed about 1 pH unit to the lowered pK a value (19). This experimental result was in good agreement with the calculations of Naor and Jensen (25) who also hypothesized that the hydrogen bond between Cys283 and the amide of Ser285 would contribute approximately 1.5 pH units. Removal of these two hydrogen bonds would be expected to increase the pK a value of Cys283 to ~8.1, which is still below the standard pK a value for a cysteine residue.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…The factors contributing to the low pK a value are not all immediately apparent, although it was shown that a S…OH bond between Cys283 and Ser285 ( Figure 2A) contributed about 1 pH unit to the lowered pK a value (19). This experimental result was in good agreement with the calculations of Naor and Jensen (25) who also hypothesized that the hydrogen bond between Cys283 and the amide of Ser285 would contribute approximately 1.5 pH units. Removal of these two hydrogen bonds would be expected to increase the pK a value of Cys283 to ~8.1, which is still below the standard pK a value for a cysteine residue.…”
supporting
confidence: 86%
“…Since the experimental geometries of the P284A and C283S/S285C mutants were not available, the structural models of the mutants were constructed from the wild type model (with Cys deprotonated) used by Naor and Jensen (25) (Figure 2B). In the case of the C283S/S285C variant the S and O atoms were interchanged ( Figure 2C).…”
Section: Protein Model Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogen bonds between amide nitrogen atoms and thiolate anions remain strong with interatomic distances of 3.4-4.0 Å. 25 Similar distances are routinely observed between the glutathione and other HPGDS inhibitors in this series. The physical properties of the compound were evaluated, and it was found that 8 had a solubility of 1.5 μg/mL (3.9 μM) at pH 6.50.…”
supporting
confidence: 75%